Honour killing in the second decade of the 21st century - Shoro, Shahnaz, 1969- (Cambridge Scholars Publishing, 2017)
Honour killing is considered the worst form of domestic violence against human beings, particularly against women. It is clear that societies across the world - through their laws and their courts - continue to countenance legal defences which overwhelmingly benefit males committing violence against females. Despite the statistics that honour killings are being reported from all over the world, the greatest number of shocking reports of honour killings come from Muslim countries. Unfortunately, Pakistan is among those countries where women are facing various forms of violence in the name of religion, customs and traditions, and cases of honour killing are regularly reported there. It is imperative to understand and see killings in the name of honour from the perspective of those who have been directly affected by the socio-religious cultural norms which condone them. The findings gathered here show that honour killing is not only family or community violence or a tradition to preserve honour, but that behind these killings ulterior purposes are being served and therefore the number of the killings is increasing every year in Pakistan. This book will allow the reader to understand precisely the menace of honour killing and to consider how it can be addressed to save innocent lives and to stop these severe violations of human rights.